1974
DOI: 10.1016/0032-0633(74)90071-3
|View full text |Cite
|
Sign up to set email alerts
|

Parametric study of near-wake structure of spherical and cylindrical bodies in the laboratory

Abstract: Some aspects of the interaction between metal bodies and streaming rarefied plasmas were studied in a newly constructed Plasma Wind Tunnel as part of an attempt to investigate (via simulation) phenomena relevant to the spacecraft/space plasma interaction. Detailed nearwake ion current profiles for both spherical and cylindrical bodies at different body potentials (&) and at different plasma flow parameters are presented. Various features of the profiles can be correlated, at least qualitatively, with both plas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
12
0
3

Year Published

1975
1975
2015
2015

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 8 publications
3
12
0
3
Order By: Relevance
“…The experimental facility is described elsewhere. 6 Of particular interest was the pressure range of from ~10~6 to ~10~5 Torr which comprises the nominal operating pressure of most plasma wind tunnels.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The experimental facility is described elsewhere. 6 Of particular interest was the pressure range of from ~10~6 to ~10~5 Torr which comprises the nominal operating pressure of most plasma wind tunnels.…”
Section: Resultsmentioning
confidence: 99%
“…In this Note, we will examine the influence of slow ions on both the ion and electron current distribution and the electron temperature in the wake of a body in a streaming plasma. The measurements were made in the Plasma Wind Tunnel Facility at NASA/MSFC, 6 which is being used to partially simulate the wake structure of a satellite in the ionosphere.…”
Section: Aiaa Journalmentioning
confidence: 99%
See 1 more Smart Citation
“…Henderson and Samir (1967) measured the current depletion in the wake with respect to the ram and Samir et al (1979 studied the asymmetry in the current distribution in the wake. Oran et al (1974) observed the increasing of the density in the near-wake region. Although study of the ion collection in the electron-filled wake of a spacecraft was performed during the Charge Hazard and Wake studies' flight experiment onboard shuttles ST-60, ST-69 (Enloe et al, 1997;Davis et al, 1999), the experiment was motivated by a high charging (up to kilovolts) of the low-Earthorbiting (LEO) spacecraft in the auroral regions which are populated with the energetic electrons.…”
Section: Introductionmentioning
confidence: 83%
“…It is well known that a charged particle or macroobject, immersed in a flowing plasma, creates a perturbed region (a wake) behind itself. [1][2][3][4][5][6][7][8][9][10][11] Wakefield potential is often invoked to explain a vertical alignment of dust particles levitating in the plasma sheath of capacitive radio-frequency (RF) discharge. In such a plasma, ions have a directed velocity relative to stationary dust particles 12 which in turn acquire a significant negative charge (10 3 -10 4 elementary charges) due to the higher electron mobility.…”
mentioning
confidence: 99%